Sistem E-Office Berbasis Web Pada Kantor Pemerintah Daerah Bagian Kesejahteraan Rakyat Kabupaten Muara Enim - Bernard Abdurrahman; Suryayusra Suryayusra (LPPM UBHINUS MALANG, 2023)
The Muara Enim Regency People's Welfare Regional Government Office faces obstacles in conventional administration. E-office systems overcome these challenges by digitally organizing incoming and outgoing mail, managing office inventory, and integrating activity agendas. The use of this system is expected to improve service quality, administrative efficiency, information accessibility, employee collaboration and responsiveness to the community. With the e-office system, the Muara Enim Regency People's Welfare Regional Government Office can improve efficiency, transparency and quality of public services. Web-based e-office systems are an effective solution for automating administration and increasing work efficiency. This research aims to measure the effectiveness of the program, analyze the factors that influence its success, and provide policy recommendations that can improve and expand the positive impact of the program, so as to provide guidance for local government decision making in an effort to improve the welfare of rural communities in a sustainable manner. Research results from the web-based E-Office system at the Muara Enim Regency People's Welfare Regional Government Office have provided a significant positive impact in increasing efficiency, transparency and quality of public services.